The February 2018 seismic swarm in São Miguel, Azores - Soares, A.; Custódio, S.; Cesca, S.; Silva, R.; Vuan, A.; Mendes, V. B. (Frontiers in Earth Science, 2023)
The island of São Miguel is among the most seismically active areas of the Azores archipelago. This work focuses on the most significant recent swarm, which occurred on February 2018. We set up an automated procedure to process continuous full seismic waveform data from local stations to generate high-quality earthquake information on the volcano unrest episode. First, we applied an automated detector software, next we located the detected events and then classified the earthquakes based on their waveform similarity, identifying three families of seismic events. We then extended the catalog by template matching. Finally, we computed moment tensors to investigate the source mechanisms of the largest earthquakes. Our results image the ~2-week swarm evolution. The activity started with a precursory phase with low rate and low magnitude (ML < 2.0) seismicity and the activation of a deeper structure (~ 10-15 km). After ~1 week, a new earthquake family emerged at shallower depths (~ 8-12 km) reaching magnitudes up to ML 3.7. Finally, a third slightly shallower family was activated. Moment tensors show mostly normal faulting mechanisms, striking ~NW-SE, compatible with the orientation of the regional stress field. A surface deformation transient was recorded by geodetic stations, starting with the swarm, and continuing over the following ~17 months, corresponding to either inflation or extension around the swarm region. The prolonged surface deformation implies a process that was initiated during the swarm and subsequently accommodated mostly aseismically. We interpret the seismicity observed at the early stage of deformation as indicating episodic fluid injection through the crust, related to the local hydrothermal or magmatic systems. We conclude that the Fogo-Congro region continues to be seismo-volcanically active, with both seismic and aseismic deformation observed and requiring close multidisciplinary monitoring. The proposed methology based on the automated analysis of continuous waveform data provides high-quality imaging of the spatio-temporal evolution of seismicity, which can be used elsewhere in the operational monitoring of seismo-volcanic crises to gain insight into the ongoing deformation processes, improve hazard assessment and help in the development of effective mitigation strategies.